Penerapan PSAK No. 16 tentang Aset Tetap pada PT. Surya Pertiwi Nusantara - Stephanie Swikno (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2021)
Business is experiencing a very rapid development in the era of globalization. A growing business will always provide demands for the reliability and relevance of the company's financial statements. Therefore, it takes appropriate standards to compare how financial statements should be presented based on applicable and generally accepted standards. In Indonesia, the standard is regulated by a professional organization that houses all Indonesian Accountants commonly referred to as the Indonesian Accounting Association (IAI) which has the authority to set guidelines in the making of accounting financial statements, namely the Statement of Financial Accounting Standards (PSAK). Each company is required to always comply with all regulations listed in the PSAK because the fairness of all company transactions refers to this standard. Pt. Surya Pertiwi Nusantara is a manufacturing company engaged in sanitary with total use of fixed assets based on its acquisition in 2020 is Rp. 688,925,058,291 of the company's total assets Of Rp. 817,588,326,530 or more than 50% of the company's total assets. Based on research, it can be concluded that overall PT. Surya Pertiwi Nusantara has implemented the guidelines well. However, there are some things that are still not fully in accordance with psak guideline number 16. Keywords : Fixed Assets, PSAK number 16